Itch in Hymenoptera Sting Reactions - Cerpes, Urban; Repelnig, Maria-Lisa; Legat, Franz J. (Frontiers in Allergy, 2021)
Insect stings and the resulting itch are a ubiquitous problem. Stings by members of the insect order Hymenoptera, which includes sawflies, wasps, bees and ants, and especially by bees and wasps are extremely common, with 56–94% of the population being stung at least once in their lifetime. The complex process of venom activity and inflammation causes local reactions with pain and pruritus, sometimes anaphylactic reactions and more seldomly, as in case of numerous stings, systemic intoxication. We reviewed the literature regarding itch experienced after Hymenoptera stings, but found no study that placed a specific focus on this topic. Hymenoptera venoms are composed of many biologically active substances, including peptide toxins and proteinaceous toxins. Peptide toxins from bee venom cause cell lysis and ion channel modulation in the peripheral and central nervous systems, while toxins from wasp venom induce mast cell degranulation and chemotaxis of polymorphonuclear leukocytes in the skin. The proteinaceous toxins cause a disruption of the cell membranes and necrotic cell death, degradation of hyaluronan (an extracellular matrix glycosaminoglycan), increased vascular permeability, hemolysis, as well as activated platelet aggregation. Mediators which could be directly involved in the venom-induced pruritus include histamine and tryptase released from mast cells, interleukin-4 and interleukin-13 from Th2 lymphocytes, as well as leukotriene C4. We postulate that a pruriceptive itch is induced due to the pharmacological properties of Hymenoptera venoms.